Successful farming
Includes various special sections or issues annually: 1968- Harvesting issue (usually no. 7 or 8); 1968- Crop planning issue (usually no. 12; title varies slightly); Machinery management issue (usually no. 2); 1970- Crop planting issue (usually no. 4; title varies slightly)